The Jurassic /Cretaceous boundary beds in Kurdistan – a preliminary note on wider correlations - W.A.P., Wimbledon; I.M.J., Mohialdeen; G, Andreini; D, Rehakova; K, Stoykova (Sulaimani Journal for Pure and Applied Sciences, 2016)
Ammonites, nannofossils and calpionellids have been studied from Chia Gara Formation at Banik village (Zakho area, Dohuk Governorate, Kurdistan). New micropalaeontological work at Banik makes it possible for the first time to identify useful western Tethyan Jurassic /Cretaceous boundary marker species (calpionellids and nannofossils) and to make precise correlations with the boundary interval in Europe and elsewhere. Kurdistan at the end of the Jurassic was positioned on the south side of Tethys, on the opposite side of that ocean from the type sites and regions for the Tithonian and Berriasian stages.
Keywords: Nannofossils,Calpionellids,Chia Gara,Banik,Kurdistan